Variation in plasma leptin levels in response to fasting in Antarctic fur seals (Arctocephalus gazella) - John Arnould; M Morris; D Rawlins; I Boyd (2002)
Plasma leptin levels were determined in 8 lactating female and 20 pup Antarctic fur seals ( Arctocephalus gazella ) during fasting periods of normal duration. Plasma leptin levels ranged from 1.35-3.19 ng·ml -1 in lactating females and 1.79-4.80 ng·ml -1 in pups and were not positively correlated with body mass or condition. A negative trend, however, was observed between plasma leptin levels and body condition in lactating females upon their arrival at the colony following a foraging trip (beginning of fast). In accordance with findings in other species, plasma leptin levels dropped significantly (P<0.02) in response to the 17-19% drop in body mass experienced by pups during fasting. In contrast, plasma leptin levels in lactating females increased during the first 24 h of fasting before decreasing throughout the remaining 48 h of the fast. This unexpected result could be due to the high level of energy expenditure by seals as they swim back to the colony (i.e. post-exercise response) or may be influenced by the intense suckling activity experienced by females during the onshore fasting periods. The results of this study support recent findings in other carnivore species which suggest the primary physiological role of leptin in these species may not necessarily be as a signal of the magnitude of body energy reserves.